2010
DOI: 10.1155/2010/106341
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Lysine Methylation in Hyperthermophilic Crenarchaea: Potential Implications for Protein Stability and Recombinant Enzymes

Abstract: In eukarya and bacteria, lysine methylation is relatively rare and is catalysed by sequence-specific lysine methyltransferases that typically have only a single-protein target. Using RNA polymerase purified from the thermophilic crenarchaeum Sulfolobus solfataricus, we identified 21 methyllysines distributed across 9 subunits of the enzyme. The modified lysines were predominantly in α-helices and showed no conserved sequence context. A limited survey of the Thermoproteus tenax proteome revealed widespread modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
52
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 29 publications
8
52
0
Order By: Relevance
“…Cren7 methylation was completely abolished when all 12 lysine residues were changed, indicating that aKMT4 is specific to lysine. These results suggest that aKMT4 is a promiscuous protein MTase with extremely low sequence bias, which is consistent with the variegated methylation pattern of Cren7 and a number of other proteins in Sulfolobus cells (28).…”
Section: Csl4-exosome and Rrp4-exosome Lanes)supporting
confidence: 79%
See 4 more Smart Citations
“…Cren7 methylation was completely abolished when all 12 lysine residues were changed, indicating that aKMT4 is specific to lysine. These results suggest that aKMT4 is a promiscuous protein MTase with extremely low sequence bias, which is consistent with the variegated methylation pattern of Cren7 and a number of other proteins in Sulfolobus cells (28).…”
Section: Csl4-exosome and Rrp4-exosome Lanes)supporting
confidence: 79%
“…We designated it as aKMT4 (belonging to the KMT4/Dot1 family of class I AdoMet-dependent MTases). Recently, Chu et al (27) also isolated and characterized the same enzyme from Sulfolobus (designated as aKMT by them) and found that it methylates Cren7 and many proteins involved in DNA replication in vitro, which correlates well with the extensive lysine methylation pattern in Sulfolobus cells (28). Our study shows that aKMT4 bears self-methylation activity and competes for a methyl group with other substrates.…”
supporting
confidence: 68%
See 3 more Smart Citations